Pengaruh Produk Domestik Regional Bruto Sektoral Terhadap Kemiskinan di Indonesia - Ilham Ksatria; Istiqomah Istiqomah; Arintoko Arintoko (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
This study aims to analyze the effect of the Gross Regional Domestic Product of the primary sector, secondary sector and tertiary sector on poverty levels in Indonesia in 2010 - 2020. This study uses a quantitative approach. Research locations in 33 provinces in Indonesia. The method used in this study is multiple linear regression panel data. The results showed that the GRDP of the primary sector and the secondary sector had a significant negative effect on the poverty level in Indonesia. The GRDP of the tertiary sector has no effect on the level of poverty in Indonesia. This finding implies increasing employment opportunities in all sectors of the economy.